Morbidity and Mortality Associated with Community used Herbal (sagwa)use in Children with Acute Gastroenteritis in Diyala Governorate - M Shukur , Ali; I Alezzi, Jalil; J Kadhim, Talib (Diyala Journal of Medicine, 2019)
Background: Gastroenteritis causes around (28%) of all mortalities among children less than 5 yr old. In our country herbal use (called sagwa in Iraq) is one of line of treatment of gastroenteritis mostly in the rural areas. Objective: To determine the morbidity and mortality of herbal use in acute gastroenteritis in children. Patients and Methods: Two hundred patients involved in a prospective case control study conducted in the Al-Batool Pediatrics, Obstetrics and Gynecology Teaching Hospital, Diyala, Iraq, during a period of six months from August 2017 to February 2018. Results: There is significant association of sagwa use with the rural residency 81(81%), mother education level 57(57%) illiterate mother), the order of the child in the family 13(13%)1st child; the least), diarrhea complications (regarding central nervous system 43(43%), cardiac 58(58%), renal 49(49%) and metabolic 83(83%), hospital stay and condition deterioration and the mortality rate was 9(9%) in sagwa group .Sagwa toxicity is positively proportional to the number of doses 57(57%) in 3rd dose & more) given to children and grandmothers 66(66%) were the principle person who decided to use sagwa in children with diarrhea. The chemical analysis was done in (10) samples only which revealed that heavy metal like lead, cadmium and mercury; that exceed the permissible level. Conclusion: There is significant morbidity and mortality caused by (sagwa) use in children with acute gastroenteritis. DOI:https://doi.org/10.26505/DJM.17024690527